2009
DOI: 10.1002/lsm.20746
|View full text |Cite
|
Sign up to set email alerts
|

High contrast near‐infrared polarized reflectance images of demineralization on tooth buccal and occlusal surfaces at λ = 1310‐nm

Abstract: Background and Objectives: Sound enamel manifests peak transparency in the near-IR (NIR) at 1310-nm, therefore the near-IR is ideally suited for high contrast imaging of dental caries. The purpose of this study was to acquire images of early demineralized enamel on the buccal and occlusal surfaces of extracted human teeth using NIR reflectance imaging and compare the contrast of those images with the contrast of images taken using other methods. Materials and Methods: Fifteen human molars were used in this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 36 publications
1
71
3
1
Order By: Relevance
“…16,18,24 In this study, we demonstrated that the sensitivity and specificity of the NIR TI technique, when compared with radiography, provided very good results. The technique can be useful for early caries diagnosis and patient follow-up, and can improve routine monitoring of enamel lesions during preventive intervention.…”
Section: Discussionmentioning
confidence: 75%
“…16,18,24 In this study, we demonstrated that the sensitivity and specificity of the NIR TI technique, when compared with radiography, provided very good results. The technique can be useful for early caries diagnosis and patient follow-up, and can improve routine monitoring of enamel lesions during preventive intervention.…”
Section: Discussionmentioning
confidence: 75%
“…In a recent imaging study, we compared the image contrast of artificially demineralized lesions produced on the buccal and occlusal surfaces on whole extracted teeth measured using various imaging methods. 18 NIR reflectance and NIR transillumination were investigated along with QLF ͑473-nm excitation͒ and visible reflectance. Crossed polarizers were used to eliminate specular reflection ͑glare͒ from tooth surfaces for the NIR and visible light reflectance measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and Fried [50] reported the high-contrast polarized reflectance images of early demineralization on buccal and occlusal tooth surfaces measured at l ¼ 1310 nm and found that the contrast between early demineralization was significantly higher at 1310 nm than in the visible range. Figure 68.4a and b show cross-polarization images of enamel demineralization in the visible and NIR region, showing the marked difference in contrast between the sound and demineralized enamel in these two spectral regions.…”
Section: Reflectance Spectroscopymentioning
confidence: 99%